2015
DOI: 10.1007/978-1-4939-2929-0_22
|View full text |Cite
|
Sign up to set email alerts
|

Bone Marrow Transplantation in Mice to Study the Role of Hematopoietic Cells in Atherosclerosis

Abstract: Hematopoietic stem cell transplantation or bone marrow transplantation is a common approach to reconstitute the immune system of mice that have been subjected to marrow-ablative doses of radiation. This method can be used in the field of atherosclerosis to assess the contribution of hematopoietic cells of a desired genotype to disease pathogenesis. The engraftment of atherosclerosis-prone mice with donor cells that contain genetic alterations in cells of the innate or adaptive immune system has been invaluable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…For bone marrow chimera studies, 6-wk-old recipient mice were irradiated twice with 600 Rad (4 h apart) and injected (i.v.) with 4 × 10 6 donor bone marrow cells, as previously described (Sreeramkumar & Hidalgo, 2015). To test for successful adoptive bone marrow cell transfer, CD45.1 (WT) and CD45.2 ( Viperin −/− ) staining on 10 μl tail blood was assessed by flow cytometry 7.5 wk post engraftment (Fig S9), virus infection was performed by ventral injection of 1 × 10 6 pfu at 8 wk post engraftment.…”
Section: Methodsmentioning
confidence: 99%
“…For bone marrow chimera studies, 6-wk-old recipient mice were irradiated twice with 600 Rad (4 h apart) and injected (i.v.) with 4 × 10 6 donor bone marrow cells, as previously described (Sreeramkumar & Hidalgo, 2015). To test for successful adoptive bone marrow cell transfer, CD45.1 (WT) and CD45.2 ( Viperin −/− ) staining on 10 μl tail blood was assessed by flow cytometry 7.5 wk post engraftment (Fig S9), virus infection was performed by ventral injection of 1 × 10 6 pfu at 8 wk post engraftment.…”
Section: Methodsmentioning
confidence: 99%
“…This approach is standard in the atherosclerosis literature and is usually interpreted as indicating myeloid specificity and even implied specificity for macrophages. [30][31][32][33][34] Recipient Ldlr -/mice were preconditioned with lethal c-irradiation, then rescued by adoptive transfer of bone marrow from mice deficient in AMPK (Prkab1 -/-) or littermate matched (Prkab1 þ/þ ) controls. BMT was performed at age 12 weeks, and metformin treatment from age 14 weeks to age 25 weeks, allowing a prolonged period on metformin after BMT, when there was a cull for analysis as for the first cohort (Figure 2A).…”
Section: Atherosclerosis-prevention By Metformin Requires Haematopoietic Ampkmentioning
confidence: 99%
“…To investigate the impact of macrophages in atherosclerosis, bone marrow transplantation in mice offers a powerful and effective strategy. This approach allows for the generation of chimeric animals with a hematopoietic compartment carrying the donor's genetic background, which enables the identification of the role of the genetic profile of these cells in the development of atherosclerosis [10]. Consistent evidence has shown that the reconstitution of Apoe −/− mice with wild-type bone marrow cells results in protection from high lipid levels and atherosclerosis, and, conversely, wild-type mice reconstitution with Apoe −/− bone marrow cells exacerbates atherosclerosis [11,12].…”
Section: Introductionmentioning
confidence: 99%